Effect of liming and nutrient management on productivity and profitability of maize (Zea mays L.) in the Northeast region of India - Raghavendra S J; Shiva Dhar; Huchchappa Jamakhandi; Anchal Dass; Lohit K. Baishaya; Kapila Shekhawat; Shashank Patel; Sudarshan S; Rakshit Gowda S P; Anita Saini (Annals of Agricultural Research, 2025)
India’s main cereal crop, maize (Zea mays L.), is limited in its yield by acidic soils and inadequate fertilizer management, especially in the Northeast region. In order to assess the impact of liming and integrated nutrient management (INM) on maize growth, yield, and economics in acidic environments, a field experiment was carried out at the ICAR–IARI in Assam during the 2024 kharif season. Three levels of lime (Control, 250 kg ha-1, and 300 kg ha-1 based on soil test (ST)) and five nutrient management treatments (Control, 100% recommended dose of fertilizer (RDF), 50% RDF combined with 50% recommended dose of nitrogen (RDN) from farmyard manure (FYM), 50% RDF combined with 50%RDN from vermicompost (VC) and 50% RDF combined with 50% RDN from poultry manure (PM)) were used in the experiment, which was conducted using a split-plot design. Among the different levels of lime, liming at 300 kg ha-1 considerably increased growth parameters, such as plant height, leaf area index (LAI), dry matter accumulation (DMA), grain yield (4.43 t ha-1), stover yield (8.6 t ha-1), and biological yield (13.03 t ha-1) in comparison to the control and 250 kg ha-1 of lime. Among nutrient management treatments, 50% RDF + 50% RDN (PM) showed highest plant height, LAI,DMA, grain yield (4.55 t ha-1), stover yield (8.59 t ha-1), and biological yield (13.14 tha- 1) compared to other treatments. Lime at 300 kg ha-1 improved gross returns (105,738 ` ha-1), net returns (69,030`ha-1), and the net B:C ratio (1.90) in comparison to the control, but it also marginally raised cultivation costs (36,708 `ha-1). Nutrient management treatments were more profitable; the maximum gross returns (108,200 ` ha), net returns (72,673 `ha-1) and net B:C ratio (2.04) were obtained with 50% RDF + 50% RDN (PM).